THM and HAA formation from NOM in raw and treated surface waters. (1st April 2017) - Golea, D.M.; Upton, A.; Jarvis, P.; Moore, G.; Sutherland, S.; Parsons, S.A.; Judd, S.J.
Abstract: The disinfection by-product (DBP) formation potential (FP) of natural organic matter (NOM) in surface water sources has been studied with reference to the key water quality determinants (WQDs) of UV absorption (UV254 ), colour, and dissolved organic carbon (DOC) concentration. The data set used encompassed raw and treated water sampled over a 30-month period from 30 water treatment works (WTWs) across Scotland, all employing conventional clarification. Both trihalomethane (THM) and haloacetic acid (HAA) FPs were considered. In addition to the standard bulk WQDs, the DOC content was fractionated and analysed for the hydrophobic (HPO) and hydrophilic (HPI) fractions. Results were quantified in terms of the yield (dDBPFP/dWQD) and the linear regression coefficient R 2 of the yield trend. The NOM in the raw waters was found to comprise 30–84% (average 66%) of the more reactive HPO material, with this proportion falling to 18–63% (average 50%) in the treated water. Results suggested UV254 to be as good an indicator of DBPFP as DOC or HPO for the raw waters, with R 2 values ranging from 0.79 to 0.82 for THMs and from 0.71 to 0.73 for HAAs for these three determinants. For treated waters the corresponding values were significantly lower at 0.52–0.67 and 0.46–0.47 respectively, reflecting the lower HPO concentration and thus UV254 absorption and commensurately reduced precision due to the limit of detection of the analytical instrument. It is concluded that fractionation offers little benefit in attempting to discern or predict chlorinated carbonaceous DBP yield for the waters across the geographical region studied. UV254 offered an adequate estimate of DBPFP based on a mean yield of ∼2600 and ∼2800 μg per cm −1 absorbance for THMFP for the raw and treated waters respectively and ∼3800 and2900 μg cm −1 for HAAFP, albeit with reduced precision for the treated waters. Highlights: Impact of clarification of surface water on DBPFP studied for THMs and HAAs. Study based on 30 WTW sites over 30 month period, and both raw and treated waters. Trends in R 2 for DBPFP vs UV254 and DOC were the same for the two DBPs. UV254 and DOC were as good an indicator of DBPFP as hydrophobic carbon concentration. Change in DBP yield from raw to treated water corresponds to change in HPO fraction.